The Impact of Operating Surgeon Experience, Supervised Trainee vs. Trained Surgeon, in Vascular Surgery Procedures: A Systematic Review and Meta-Analysis. (August 2019) - Bath, Michael F.; Awopetu, Ayoola I.; Stather, Philip W.; Sadat, Umar; Varty, Kevin; Hayes, Paul D.
Abstract : Objective: The operative caseload of a surgeon has a positive influence on post-operative outcomes. For surgical trainees to progress effectively, maximising operating room exposure is essential, vascular surgery being no exception. Our aim was to ascertain the impact of supervised trainee led vs. expert surgeon led procedures on post-operative outcomes, across three commonly performed vascular operations. Methods: A literature search was undertaken using the MEDLINE, Web of Science, and Cochrane databases up to 1 January 2018. Studies reporting outcomes following major lower limb amputation, fistula formation, or carotid endarterectomy (CEA) that involved a direct comparison between supervised trainee and experts were included, with odds ratios (ORs) calculated. Primary outcomes varied depending on the specific procedure: amputations—rate of amputation revision within 30 days; fistula formation—primary patency; CEA—stroke rate at 30 days. Meta-analysis with the Mantel-Haenszel method was performed for each outcome. Results: Sixteen studies were included in the final review. Overall, trainees accounted for a third of all procedures analysed ( n  = 2 421/7 017; 34.5%). Only one study was identified that described rates of amputation revision, precluding any further analysis. Four studies on fistula formation were included, showing no significant difference in outcomes between trainees and experts in primary patency (OR 1.68, 95% confidence interval [CI] 0.42–6.75). Nine studies were identified reporting post-CEA stroke rates, also demonstrating no difference between trainees and experts (OR 0.89, 95% CI 0.59–1.32). Conclusion: In select cases, with appropriate training and suitable experience, supervised trainees can perform surgical procedures without any detriment to patient care. To ensure high standards for patients of the future, supported training programmes are essential for today's surgical trainees.